Innovative tools and design strategies The case of Eclectic Architecture in Buenos Aires - Andrés Garrido, Federico (KIT Scientific Publishing, 2023)
The research deals with a question about Architecture and its design strategies, combining historical information and digital tools. Design strategies are historically defined, they rely on geometry, context, building technologies and other factors. The study of Architecture´s own history, particularly in the verge of technological advancements, like the introduction of new materials or tools may shed some light on how to internalize digital tools like parametric design and digital fabrication.